Engaging More Effectively With Visitors to Coastal Regions for Improved Management Outcomes: Insights From the Ningaloo Coast, Australia - Cvitanovic, Christopher; van Putten, E. Ingrid; Kelly, Rachel; Feldman, Hannah R.; van Steveninck, Tatiana J.; Mackay, Mary; Badullovich, Nicholas; Gourlay, Tegan (Frontiers in Marine Science, 2020)
A key component of successful coastal management efforts is an effective communication and engagement strategy focused on raising awareness of a region to different stakeholders to encourage more pro-environmental behaviours. Accordingly, in recent times there has been a proliferation of research focused on improving engagement and communication with different users of the coastal environment. Despite this effort, a paucity of evidence is available to guide better communication and engagement with visitors (i.e. tourists). Addressing this knowledge gap is critical given the adverse impacts of current global coastal tourism on ecosystem health, and projected future increases in coastal tourism. Using a case study of the Ningaloo Coast World Heritage Area (WHA) in Australia, we contribute towards filling this gap by identifingidentifyingy visitors' perception of the region and their self-reported and intended pro-environmental behaviours. We also identify the types of information they access and trust, and explore whether different message framings on the value of the WHA influence visitors’ intended pro-environmental behaviour. We determine that although visitors to the Ningaloo Coast WHA are optimistic about the future sustainability of the region, they have low understanding of the rules and regulations in place to support its management. Further, we find that visitors consider tourism to be a serious threat to the future of the region. However, most participants in our study considered the quality of their own environmental behaviour to be high, and thus not contributing to these threats, although this did differ by gender. Finally, we highlight that visitors to the Ningaloo Coast WHA, for the most part, obtain their knowledge of the region during their visit, primarily through local signage and visitors centres. We discuss the implications of these results, and highlight future considerations for coastal managers when developing visitor-focused communication and engagement strategies.